Intersecting and dynamic gender rights to néré, a food tree species in Burkina Faso - Pehou, Catherine; Djoudi, Houria; Vinceti, Barbara; Elias, Marlène (Elsevier, 2020)
This study examines women's bundles of rights to exploit the pods of a valuable food-tree species in Burkina Faso, Parkia biglobosa, locally known as néré. In West Africa, néré pods have traditionally been collected and processed by women and sold as soumbala, a highly-valued condiment. Given its value to local livelihoods, néré is a prized tree that is subject to a particular tenure regime. This study investigates the social factors that define women's harvesting rights to néré pods in the centre-west region of Burkina Faso through the lens of intersectionality. Whereas customary land tenure in Burkina Faso grants men primary ownership and use rights to land, different groups of women are entitled to harvest food-tree products such as néré pods, in defined spaces. This study shows how women, who are usually presented as a homogeneous group in terms of rights, are socially differentiated on the basis of several factors, such as residence status, ethnicity and seniority within their lineage. This differentiation shapes the nested bundles of rights held by different groups of women on different land types. Amid broad-ranging demographic, market, and environmental changes, rights to exploit néré pods are shifting and contested, and insecurity of rights challenges the sustainability and equitability of néré harvesting.